The Evolution of Criminal Punishment Theory: From Retributive Theory to a Restorative Approach in The Indonesian Criminal Justice System - Mardana Rifta Oktaviana; Ali Masyhar; Cahya Wulandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the evolution of criminal punishment theory from a retributive orientation toward a restorative approach within the Indonesian criminal justice system and analyzes its implications for contemporary criminal justice reform. The research employed a normative legal method using conceptual and statutory approaches. Primary legal materials consisted of Law Number 1 of 2023 concerning the Criminal Code, Attorney General Regulation Number 15 of 2020, and Supreme Court Regulation Number 1 of 2024, while secondary materials included scholarly literature on punishment theory and restorative justice. The findings indicate that the development of punishment theory has contributed to a fundamental transformation in the objectives of criminal law, shifting emphasis from retaliation toward recovery, accountability, and social reconciliation. This transformation has encouraged the institutionalization of restorative justice across various stages of criminal justice administration and strengthened the pursuit of substantive justice. However, effective implementation remains challenged by regulatory fragmentation, limited institutional capacity, persistent punitive legal culture, unequal bargaining positions, and potential abuse of discretion. The study concludes that restorative justice possesses significant potential to become a dominant paradigm within the Indonesian criminal justice system, provided that future reforms focus on institutional coherence, victim protection, professional capacity development, and comprehensive monitoring mechanisms.